2019
DOI: 10.1130/g46153.1
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide oxidation affects the preservation of sulfur isotope signals

Abstract: The accumulation of oxygen in Earth’s atmosphere and oceans in the late Archean had profound implications for the planet’s biogeochemical evolution. Oxygen impacts sulfur cycling through the oxidation of sulfide minerals and the production of sulfate for microbial sulfate reduction (MSR). The isotopic signature of sulfur species preserved in the geologic record is affected by the prevailing biological and chemical processes and can therefore be used to constrain past oxygen and sulfate concentrations. Here, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
(16 reference statements)
3
4
1
Order By: Relevance
“…This was significantly higher than the apparent enrichment factor that was obtained here (i.e., −25.6‰), which meant that sulfide oxidation reduced the apparent isotopic fractionation. This observation was consistent with that of Findlay et al but was distinct from that of Pellerin et al, who found that an active oxidative sulfur cycle in Mangrove Lake (Bermuda) could significantly increase the fractionation of the measured values. This difference was due to sulfur disproportionation being dominant in Pellerin et al, which resulted in a large apparent isotopic fractionation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This was significantly higher than the apparent enrichment factor that was obtained here (i.e., −25.6‰), which meant that sulfide oxidation reduced the apparent isotopic fractionation. This observation was consistent with that of Findlay et al but was distinct from that of Pellerin et al, who found that an active oxidative sulfur cycle in Mangrove Lake (Bermuda) could significantly increase the fractionation of the measured values. This difference was due to sulfur disproportionation being dominant in Pellerin et al, which resulted in a large apparent isotopic fractionation.…”
Section: Resultssupporting
confidence: 92%
“…This difference was due to sulfur disproportionation being dominant in Pellerin et al, which resulted in a large apparent isotopic fractionation. In Findlay et al . and our study, sulfur disproportionation and its isotopic effects were negligible, as discussed above.…”
Section: Resultssupporting
confidence: 81%
“…Although we cannot assess the extent to which secondary postdepositional processes have affected the original sedimentary sulfur isotope pattern, we expect this effect to be minimal and it is clear that surface sediment δ 34 S preserve the atypical nature of the sulfur isotopic pattern observed in the water column, that is, higher sulfide δ 34 S than sulfate δ 34 S. These results suggest that despite some overprint on sedimentary primary sulfur isotope composition by secondary oxidative processes, surface sediment δ 34 S are inherited from water column δ 34 S and inform on the Dziani Dzaha sulfur cycle. This contrasts with some other studies highlighting a complete overprint of primary signature by secondary processes (e.g., Findlay et al, 2019).…”
Section: Significance Of the "Superheavy Pyrite" Signature Of The Dzi...contrasting
confidence: 99%
“…This could indicate that the leaching of pyrite veins, only reported in Triassic series at depth, can be a supplementary source of sulfur to the caves. Abiotic oxidation of sulfides may induce a small δ 34 S fractionation up to 5‰ (Fry et al, 1988;Findlay et al, 2019), which can be compatible with the signature of the cave gypsum Erm1. A thermodynamic model was performed using the PhreeqC software (Parkhurst and Appelo, 1999) and using the SUPCRT92 database (Johnson et al, 1992), to determine the concentration of sulfides released during pyrite oxidation between 25 and 200 °C.…”
Section: A Thermochemical Production Of H 2 S At Depthsupporting
confidence: 56%